Cortical and subcortical glutathione levels in adults with autism spectrum disorder. Issue 4 (20th August 2015) - Durieux, Alice M.S.; Horder, Jamie; Mendez, M. Andreina; Egerton, Alice; Williams, Steven C. R.; Wilson, C. Ellie; Spain, Debbie; Murphy, Clodagh; Robertson, Dene; Barker, Gareth J.; Murphy, Declan G.; McAlonan, Grainne M.
Abstract : Increased oxidative stress has been postulated to contribute to the pathogenesis of autism spectrum disorder (ASD). However, reports of alterations in oxidation markers including glutathione (GSH), the major endogenous antioxidant, are indirect, coming from blood plasma level measurements and postmortem studies. Therefore we used in‐vivo 3 Tesla proton magnetic resonance spectroscopy ([1H]MRS) to directly measure GSH concentrations in the basal ganglia (BG) and the dorsomedial prefrontal cortex of 21 normally intelligent adult males with ASD and 29 controls who did not differ in age or IQ. There was no difference in brain GSH between patients and controls in either brain area; neither did GSH levels correlate with measures of clinical severity in patients. Thus [1H]MRS measures of cortical and subcortical GSH are not a biomarker for ASD in intellectually able adult men. Autism Res 2016, 9: 429–435 . © 2015 The Authors Autism Research published by Wiley Periodicals, Inc. on behalf of International Society for Autism Research.